Renewable energy - Labrecque, Ellen (Labrecque, Ellen. Global citizens: environmentalism., 2018)
Examines renewable energy sources around the world through the lenses of history, geography, civics, and economics. Includes tips for using evidence from a variety of sources to form conclusions, color photographs, a glossary, critical thinking questions, and further resources.